2008
DOI: 10.5194/acp-8-1261-2008
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the specific surface area of snow with X-ray tomography and gas adsorption: comparison and implications for surface smoothness

Abstract: Abstract. Chemical and physical processes, such as heterogeneous chemical reactions, light scattering, and metamorphism occur in the natural snowpack. To model these processes in the snowpack, the specific surface area (SSA) is a key parameter. In this study, two methods, computed tomography and methane adsorption, which have intrinsically different effective resolutions -molecular and 30 µm, respectively-were used to determine the SSA of similar natural snow samples. Except for very fresh snow, the two method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 59 publications
3
104
0
Order By: Relevance
“…estimated it at 10%, leading to an overall error of 12%. However, Kerbrat et al (2008) showed that the CH 4 adsorption method gave results within 3% of X-ray tomography, so that it is reasonable to suggest that the systematic error due to CH 4 adsorption is 5% or less. In that case, combining a random error of 8% and a systematic error of 5%, we conclude that the uncertainty of SSA determination using IR hemispherical reflectance at 1310 nm under the current conditions is 10%.…”
Section: Recommendation For Snow With Ssa<60 M 2 Kg −1mentioning
confidence: 99%
See 1 more Smart Citation
“…estimated it at 10%, leading to an overall error of 12%. However, Kerbrat et al (2008) showed that the CH 4 adsorption method gave results within 3% of X-ray tomography, so that it is reasonable to suggest that the systematic error due to CH 4 adsorption is 5% or less. In that case, combining a random error of 8% and a systematic error of 5%, we conclude that the uncertainty of SSA determination using IR hemispherical reflectance at 1310 nm under the current conditions is 10%.…”
Section: Recommendation For Snow With Ssa<60 M 2 Kg −1mentioning
confidence: 99%
“…The smaller structures are easily perturbed by the liquid and by microtoming, and are often unresolved by optical photography. Lastly, X-ray tomography can also produce SSA values (Flin et al, 2003;Kerbrat et al, 2008;Kaempfer and Schneebeli, 2007) but this is not easy to use in the field and the resolution is currently insufficient if SSA>70 m 2 kg −1 (Kerbrat et al, 2008), a value frequently exceeded in fresh snow.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Specific surface area (SSA) [Kerbrat et al, 2008] is the ratio of ice surface area over ice volume (unit m À1 ). The surface area was extracted from the voxel data using a marching cubes algorithm [Lorensen and Cline, 1987].…”
Section: Specific Surface Areamentioning
confidence: 99%
“…In snow science, the most popular denoising filter is the Gaussian filter (e.g. Kerbrat et al, 2008;Lomonaco et al, 2011;Theile et al, 2009;Schleef and Löwe, 2013), which consists in convoluting the intensity field I (i.e. the greyscale value) with a Gaussian kernel of zero mean N (0, σ ) defined as…”
Section: Denoising With a Gaussian Filtermentioning
confidence: 99%